BUREAUCRACY CAPACITY OF LOCAL GOVERNMENTS FOR THE IMPLEMENTATION OF PUBLIC SERVICES: A LITERATURE STUDY - Anwar Sadat; Rian Andika (Jurnal Studi Ilmu Pemerintahan, 2022)
The purpose of this study was to evaluate the capacity of the government bureaucracy in public services. This means that the government is domiciled as a powerful organization that performs actions based on its authority and as a public legal entity that can provide services whose impact is felt directly by the community. One type of government activity as a strong organization is to provide services to the community. This is because of the acceptance of the notion of a Welfare State in the Indonesian constitution, as underlined in the fourth paragraph of the Preamble to the 1945 Constitution, that one of the goals of the State is to promote general welfare. However, public satisfaction with government bureaucratic services is still low; In this regard, it is necessary to examine the role of the government bureaucracy as a public service provider to find solutions in overcoming public service constraints and guaranteeing public relations with the government bureaucracy as a public service provider.